Effects Of Post-Deposition Annealing Time In Forming Gas Ambient On Y2O3 Films Deposited On Silicon Substrate - Hock, Jin Quah; Kuan, Yew Cheong; Hassan, Zainuriah; Way, Foong Lim (2019)
The effects of post-deposition annealing (PDA) time (15, 30, and 45 min) at 800˚C in forming gas (95% N2-5% H2) ambient was systematically studied for RF-magnetron sputtered Y2O3 films on n-type Si(100) substrate. X-ray diffraction characterization has revealed the detection of Y2O3 phase oriented in (400), (440), (541), and (543) planes for all of the investigated samples. Atomic force microscopy was utilized to acquire 2-dimensional surface topograpy of Y2O3 films subjected to different PDA time. An increment in rootmean-square roughness was perceived as PDA time was prolonged. In addition, currentvoltage and capacitance-voltage characteristics of the investigated Al/Y2O3/Si-based metaloxide-semiconductor capacitors were also presented in this work.